Severe oral mucositis relating to pain and worse oral condition among patients with solid tumors undergoing treatment with FOLFIRI and 5-FU: a retrospective study - Almeida, Laura Costa de; Orcina, Bernardo da Fonseca; Maciel, Aloizio Premoli; Santos, Dayanne dos; Manzano, Brena Rodrigues; Santos, Paulo Sérgio da Silva (São Paulo Medical Journal, 2022)
BACKGROUND: There is a need for studies that correlate the severity of oral mucositis (OM) with chemotherapy protocols, transient myelosuppression and oral health. OBJECTIVE: To analyze the severity of OM among individuals with solid tumors during hospitalization and its correlation with the type of chemotherapy, myelosuppression and oral health condition. DESIGN AND SETTING: Retrospective study at a public hospital in Bauru, state of São Paulo, Brazil, that is a regional referral center. METHODS: Individuals diagnosed with solid malignant tumors who received chemotherapy during hospitalization for completion of the antineoplastic treatment cycle or who presented complications resulting from this were assessed. RESULTS: Twenty-eight individuals (24.3%) manifested some degree of OM. The most prevalent degrees of OM according to the World Health Organization (WHO) and modified WHO classification were grades 2 (11.3%) and 5 (4.3%), respectively. It was observed that the higher the OM-WHO (P < 0.001; r = 0.306) and modified OM-WHO (P < 0.001; r = 0.295) classifications were, the greater the oral pain reported by the individuals was. Presence of mucositis in the upper lip and buccal mucosa contributed to increased severity of OM and worsening of swallowing during hospitalization. Thus, severe OM was associated with use of the FOLFIRI protocol (folinic acid, fluorouracil and irinotecan). CONCLUSION: Individuals with tumors who presented severe OM had greater severity of oral pain and worse oral health. Use of the FOLFIRI protocol was associated with higher prevalence of severe OM, while use of 5-fluorouracil (5-FU) was correlated with worse oral condition.